Increased complement C1q level marks active disease in human tuberculosis. - Yi Cai (Public Library of Science (PLoS), 2014)
Background Complement functions as an important host defense system and complement C5 and C7 have been implicated in immunopathology of tuberculosis. However, little is known about the role of other complement components in tuberculosis. Methods Complement gene expression in peripheral blood mononuclear cells of tuberculosis patients and controls were determined using whole genome transcriptional microarray assays. The mRNA and protein levels of three C1q components, C1qA, C1qB, and C1qC, were further validated by qRT-PCR and enzyme-linked immunosorbent assay, respectively. The percentages of C1q expression in CD14 positive cells were determined by flow cytometry. Finally, C1qC protein level was quantified in the pleural fluid of tuberculosis and non-tuberculosis pleurisy. Results C1q expression increases significantly in the peripheral blood of patients with active tuberculosis compared to healthy controls and individuals with latent TB infection. The percentage of C1q-expressing CD14 positive cells is significantly increased in active TB patients. C1q expression in the peripheral blood correlates with sputum smear positivity in tuberculosis patients and is reduced after anti-tuberculosis chemotherapy. Notably, receiver operating characteristic analysis showed that C1qC mRNA levels in peripheral blood efficiently discriminate active from latent tuberculosis infection and healthy controls. Additionally, C1qC protein level in pleural effusion shows improved power in discriminating tuberculosis from non-tuberculosis pleurisy when compared to other inflammatory markers, such as IL-6 and TNF-α. Conclusions C1q expression correlates with active disease in human tuberculosis. C1q could be a potential diagnostic marker to discriminate active tuberculosis from latent tuberculosis infection as well as tuberculosis pleurisy from non-tuberculosis pleurisy.